Effect of pulsing ultrasound on phacoemulsification efficiency. Issue 11 (November 2015) - Gardiner, Gareth L.; Garff, Kevin; Gupta, Isha; Kramer, Gregory D.; Farukhi, Aabid M.; Stagg, Brian C.; Zaugg, Brian; Olson, Randall J.
Abstract : Purpose : To evaluate pulse type technology used to remove lens fragments during phacoemulsification. Setting : John A. Moran Eye Center Laboratories, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Lens nuclei soaked in 10 mL of 10% neutral buffered formalin for 2 hours were placed in 10 mL of balanced salt solution. Lenses were cut into 2 mm × 2 mm cubes; no more than 36 hours later, cubes were randomly selected for testing. Two aspiration and 2 vacuum settings were assessed at moderate‐ and high‐flow and vacuum (30 mL/min and 300 mm/Hg, low‐flow vacuum; 50 mL/min and 500 mm/Hg, high‐flow vacuum), with continuous 50 milliseconds on and off (long pulse) and 6 milliseconds on and off (micropulse) ultrasound. Results : There was a significant difference in efficiency favoring micropulse compared with combined long pulse and continuous pulse in high‐flow vacuum at 80% power ( P = .018) and between combined long pulse and continuous pulse versus micropulse in high‐flow vacuum at 20% power ( P = .019). Low‐flow vacuum micropulse was more efficient than continuous (19.7%) ( P < .0001) and long pulse (22.7%) ( P < .0001). Continuous and long pulses were not significantly different from one other. There was a significant difference in chatter rates between high‐flow vacuum and low‐flow vacuum when all results were compared ( P < .0001), with no additional significant differences found. Conclusion : Micropulse technology was better than continuous and long pulse at moderate but not high‐flow and vacuum settings. At the higher setting, chatter was observed less often, with all modalities more efficient than the lower setting.